2019
DOI: 10.1044/2019_jslhr-s-18-0497
|View full text |Cite
|
Sign up to set email alerts
|

How Vocal Emotions Produced by Children With Cochlear Implants Are Perceived by Their Hearing Peers

Abstract: Purpose Cochlear implants (CIs) transmit a degraded version of the acoustic input to the listener. This impacts the perception of harmonic pitch, resulting in deficits in the perception of voice features critical to speech prosody. Such deficits may relate to changes in how children with CIs (CCIs) learn to produce vocal emotions. The purpose of this study was to investigate happy and sad emotional speech productions by school-age CCIs, compared to productions by children with normal hearing (NH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
0
12
0
5
Order By: Relevance
“…Differences in the prosody of read or scripted speech as opposed to spontaneous speech have been reported in the literature (Laan, 1997). Although Damm et al (2019) found that these methods evoked highly identifiable emotions in the CNH, ANH, and ACI groups, the differences between laboratory-recorded and naturally spoken emotional speech may further modify the group differences observed here. These limitations should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Differences in the prosody of read or scripted speech as opposed to spontaneous speech have been reported in the literature (Laan, 1997). Although Damm et al (2019) found that these methods evoked highly identifiable emotions in the CNH, ANH, and ACI groups, the differences between laboratory-recorded and naturally spoken emotional speech may further modify the group differences observed here. These limitations should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 62%
“…In a recent investigation (Damm et al, 2019), the identifiability of these identical recordings made by the same participants was measured by asking normally hearing child and adult listeners to indicate whether each recording sounded happy or sad. In contrast to the normally hearing talkers and the postlingually deaf adult talkers, the CCI group’s recordings showed deficits in how well their recorded emotions were identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CI children are a paradigmatic model for the study of emotion recognition skills, as due to the early acquisition of deafness, they learned language through the degraded input of the CI, which greatly affects harmonic pitch perception. This ability is strongly necessary for emotion recognition in voices, and its deficiency could have implications on how child CI users learn to produce vocal emotions ( Damm et al, 2019 ). However, a very recent study provided evidence that also deaf people can develop skills for emotional vocalizations despite the presence of some differences in comparison to NH adults ( Sauter et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%